SEMICONDUCTOR DEVICE, MEASUREMENT SYSTEM AND MEASUREMENT METHOD - TERUAKI UEHARA (2019)
The present invention provides a semiconductor device, a measurement system, and a measurement method capable of accurately measuring biological information without referring to body data even when the shape of a surface portion in contact with a contact terminal changes. The semiconductor device including: a signal source (30) that generates a sine wave signal; an output section that outputs a measurement signal corresponding to the sine wave signal to a test subject via a first electrode (13-1); an input section that receives, as an input signal, the measurement signal that has passed through the test subject and been input via a second electrode (13-2); a first calculation device (31) that calculates correlation values between the sine wave signal and the input signal; and a second calculation section that, based on the correlation values, calculates a bioelectrical impedance of the test subject. 提供即使在与接触端子接触的表面部位的形状变化的情况下也能够正确地并且不参照身体的数据来测量生物体信息的半导体装置、测量系统以及测量方法。包含：信号源(30)，其产生正弦波信号；输出部，其经由第一电极(13－1)对受检者输出